2017
DOI: 10.30871/jagi.v1i01.360
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Aerial Photogrammetric Mapping System Overview and Image Acquisition Using Unmanned Aerial Vehicles (UAVs)

Abstract: Aerial photogrammetry is one of the Alternative technologies for more detailed data, real time, fast and cheaper. Nowadays, many photogrammetric mapping methods have used UAV / unmanned drones or drones to retrieve and record data from an object in the earth. The application of drones in the field of geospatial science today is in great demand because of its relatively easy operation and relatively affordable cost compared to satellite systems especially high - resolution satellite imagery.  This research aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 0 publications
1
5
0
2
Order By: Relevance
“…The results indicated that there was a total of 81804.4 m 3 cut and 74.2 m 3 fill along the sample road alignment (Figure 8). The most recent studies conducted in the subject of cut and fill volume computations using UAVs had some similarities with the present study (Akgül et al, 2017;Anurogo et al, 2017). The UAVs used in these studies differ in terms of their hardware and technical features and costs.…”
Section: Resultssupporting
confidence: 56%
“…The results indicated that there was a total of 81804.4 m 3 cut and 74.2 m 3 fill along the sample road alignment (Figure 8). The most recent studies conducted in the subject of cut and fill volume computations using UAVs had some similarities with the present study (Akgül et al, 2017;Anurogo et al, 2017). The UAVs used in these studies differ in terms of their hardware and technical features and costs.…”
Section: Resultssupporting
confidence: 56%
“…Photogrammetry is a method of mapping objects on the surface of the earth by using aerial photographs as a medium. Furthermore, object interpretation and geometric measurements are conducted to produce line, digital, and photomaps [14], [15]. According to [13], photogrammetry is a geoinformation technology that is carried out by using geospatial data obtained through aerial photography.…”
Section: Methods 21 Basic Concepts Of Aerial Photographsmentioning
confidence: 99%
“…kawasan mangrove dapat diidentifikasi dengan menggunakan teknologi penginderaan jauh, dimana letak geografi hutan mangrove yang berada pada daerah peralihan darat dan laut memberikan efek perekaman yang khas jika dibandingkan obyek vegetasi darat lainnya (Anurogo et al, 2005). Salah satu penginderaan jauh yang efisien serta akurat digunakan adalah fotogrametri jenis UAV (Anurogo et al, 2017).…”
Section: Pendahuluanunclassified